Light‐Induced Cold Marangoni Flow for Microswarm Actuation: From Intelligent Behaviors to Collective Drug Delivery (Laser Photonics Rev. 16(12)/2022). Issue 12 (8th December 2022) - Shi, Yang; Wang, Danning; Xiao, Yuqing; Pan, Ting; Lu, Dengyun; Zhu, Guoshuai; Xiong, Jianyun; Li, Baojun; Xin, Hongbao
Abstract : Intelligent Microswarms In article number 2200533, Yang Shi, Hongbao Xin, and colleagues proposed the light‐induced cold Marangoni flow (CMF) technique and applied it for photothermal damage‐free actuation of intelligent microrobotic swarms with strong universality and intelligent behaviors. The distinctive photothermal isolation capability of CMF ensures the microrobotic swarm to execute multiple biomedical tasks such as collective gene delivery and targeted cell chemotherapy/regulation.